PENGARUH KOMITMEN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI ASN PADA KANTOR KECAMATAN MANGARAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Febriyanto, Arik; Arief, Mohammad Yahya; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Information technology development has penetrated the government world, where almost all agencies have used technology in data processing and report-making. Information technology can overhaul a system so that the government becomes more transparent and accountable in providing and presenting services oriented to the public interest. The development of information technology in the government environment has an essential role in providing convenience in various aspects of public service activities. Implementing information technology into various public services in the government has strategic values and is considered capable of conquering difficulties in changing the work culture for the better. Based on the results of the analysis and discussion previously described, several conclusions can be drawn from the overall research results, namely as follows: Work commitment has a significant positive effect on job satisfaction, work environment has a significant positive effect on job satisfaction, work commitment has a significant positive effect on performance, work environment has a negative insignificant effect on performance, job satisfaction has a significant positive effect on performance, work commitment to performance through job satisfaction has a significant positive effect, work environment to performance through job satisfaction has a significant positive effect.